2012
DOI: 10.1542/peds.2012-0900n
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Conditions in Children With Autism Spectrum Disorder: Developing a Research Agenda

Abstract: Autism spectrum disorders (ASDs) are a set of complex neurodevelopmental disorders defined behaviorally by impaired social interaction, delayed and disordered language, repetitive or stereotypic behavior, and a restricted range of interests. ASDs represent a significant public health issue with recent estimates indicating that as many as 1% of children in the United States are diagnosed with an ASD. 1,2 Many individuals with ASDs have symptoms of associated medical conditions, including seizures, sleep problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(140 citation statements)
references
References 85 publications
2
135
0
3
Order By: Relevance
“…144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota. In a clinical study, oral vancomycin was used as a minimally absorbed antibiotic to treat the GI problems, based on this theory.…”
Section: Emerging Areasmentioning
confidence: 99%
“…144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota. In a clinical study, oral vancomycin was used as a minimally absorbed antibiotic to treat the GI problems, based on this theory.…”
Section: Emerging Areasmentioning
confidence: 99%
“…In any case the high prevalence of the GI manifestations [16,17] highlight the possibility that they might may be linked to gut dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Embora o autismo seja uma doença multifatorial, distúrbios no trato GI estão associados à prevalência e severidade de sintomas da doença (95,96). Por exemplo, estudos com o objetivo de investigar o trato GI de pacientes autistas encontraram anormalidades na motilidade gástrica e aumento da permeabilidade intestinal, além de alterações na composição da flora (97,98).…”
Section: Como a Flora Intestinal Pode Afetar O Sncunclassified